High immune cell infiltration predicts improved survival in cholangiocarcinoma - Wirta, Erkki-Ville; Szeto, Säde; Koppatz, Hanna; Nordin, Arno; Mäkisalo, Heikki; Arola, Johanna; Sirén, Jukka; Ahtiainen, Maarit; Böhm, Jan; Mecklin, Jukka-Pekka; Sallinen, Ville; Seppälä, Toni T. (Frontiers in Oncology, 2024)
Antitumoral immune response has a crucial role in constraining cancer. However, previous studies on cholangiocarcinoma (CCA), a rare and aggressive cancer, have reported contradictory findings on the prognostic impact of tumour-infiltrating T-lymphocytes. We aimed to clarify the effect of tumour-infiltrating CD3+ and CD8+ lymphocytes and PD-1/PD-L1 expression on CCA prognosis. Methods CD3+, CD8+, and PD-1+ lymphocyte densities, as well as PD-L1 expression rate were analysed from stained tissue microarray samples from the tumour centre and invasive margin of 47 cholangiocarcinomas. The association of CD3+ and CD8+ based Immune cell score (ICS) and its components with overall survival was evaluated, adjusting for age, sex, TNM stage, radicality of surgery, tumour location, and PD-L1 expression on immune cells.Low ICS was a strong independent prognostic factor for worse overall survival (Hazard ratio 9.27, 95% confidence interval 2.72-31.64, P<0.001). Among the ICS components, high CD8+ lymphocyte infiltration at the tumour centre had the most evident impact on patient outcome. PD-1 and PD-L1 expression on immune cells did not have a significant impact on overall survival alone; however, PD-L1 positivity seemed to impair survival for ICS low subgroup.Identifying patient subgroups that could benefit from immunotherapy with PD-1/PD-L1 pathway blockade may help improve treatment strategies for this aggressive cancer. Our findings highlight the importance of evaluating the immune contexture in cholangiocarcinoma, as ICS serves as a strong independent prognostic and selective factor for patients who might benefit from immunotherapy.